Analogi Morfologi, Sintaksis, dan Semantik sebagai Pilar Linguistik Arab serta Implikasinya terhadap Pedagogi Modern - Wiwin; Nisa, Khoirun; 'Aini, Nancy Mursalati; Riyadi, Sugeng; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2025)
This article explores the interrelation between morphology (?arf), linguistic synthesis (na?wu), and semantics (dal?lah) within the framework of Fiqh Lughah as the pillars of Arabic linguistics. Using qualitative and analytical methods, it highlights how classical Arabic linguistics provides analogies that are still relevant for modern pedagogy. Morphology is conceptualized as the organic structure of language, synthesis as its systemic architecture, and semantics as its vital energy. These analogies not only illustrate the depth of classical Arabic linguistic thought but also offer a foundation for developing integrative teaching methods in contemporary classrooms. Findings show that traditional pedagogy often focuses excessively on rote memorization of patterns without connecting them to communicative use. By integrating morphology, syntax, and semantics in a holistic manner, modern pedagogy can foster more effective and meaningful Arabic learning. This research contributes to bridging classical scholarship and 21st-century educational needs, especially in the digital era where language learning requires contextual, communicative, and technology-enhanced approaches.